Novel surgical techniques, regenerative medicine, tissue engineering and innovative immunosuppression in kidney transplantation - Nowacki, Maciej (Arch Med Sci, 2016)
On the 60(th) anniversary of the first successfully performed renal transplantation, we summarize the historical, current and potential future status of kidney transplantation. We discuss three different aspects with a potential significant influence on kidney transplantation progress: the development of surgical techniques, the influence of regenerative medicine and tissue engineering, and changes in immunosuppression. We evaluate the standard open surgical procedures with modern techniques and compare them to less invasive videoscopic as well as robotic techniques. The role of tissue engineering and regenerative medicine as a potential method for future kidney regeneration or replacement and the interesting search for novel solutions in the field of immunosuppression will be discussed. After 60 years since the first successfully performed kidney transplantation, we can conclude that the greatest achievements are associated with the development of surgical techniques and with planned systemic immunosuppression.